تأثير إضافة بعض مكمِّلات النمو إلى وسط الكومبوست في إنتاجية الفطر الزراعي (J.Lange) Imbach Agaricus bisporus تأثير إضافة بعض مكمِّلات النمو - زيدان, رياض; يبرق, محمد; الياس, إنعام (Latakia University Journal -Biological Sciences Series, 2019)
تمت دراسة تأثير إضافة مكملات النمو( كسبة القطن، وكسبة فول الصويا، ونخالة القمح) إلى وسط الكومبوست بالنسب (3%، و6%، و9%) من الوزن الجاف للكومبوست، وفي موعدين؛ الأول: عند زراعة الميسيليوم في وسط الكومبوست، والثاني: بعد انتهاء مرحلة الحضن (عند التغطية) في إنتاجية الفطر الزراعي الأسبوعية، والكلية خلال فترة الإنتاج. تبين نتائج الدراسة أن إضافة مكملات النمو إلى وسط الكمبوست في جميع المعاملات قد أدت إلى زيادة كمية الإنتاج، بفروق معنوية قياساً بالشاهد، في كلا الموعدين. وقد تفوقت معاملة إضافة كسبة القطن بنسبة 9% في هذا المجال على الشاهد، وجميع المعاملات الأخرى، بفروق معنوية، وبإنتاج بلغ 36.9كغ/100كغ كمبوست, وتبوأت معاملات كسبة فول الصويا، وكسبة القطن بنسبة 6% المرتبة التالية (34.25، و34 كغ/100كغ كمبوست) على التوالي. أشارت النتائج إلى تفوق موعد إضافة المكملات معنوياً قبل التغطية (32.44 كغ/100كغ كومبوست) على موعد الإضافة عند زراعة الميسيليوم ( 30.2 كغ/100كغ كومبوست) وتبينت زيادة في كمية الإنتاج في الأسبوع الأول عند موعدي الإضافة، وتفوق موعد إضافة مكملات النمو عند التغطية على موعد الإضافة عند زراعة الميسيليوم في وسط الكومبوست، ولوحظ الانخفاض في كمية الإنتاج تدريجياً حتى وصل إلى أدنى مستوى في الأسبوع الخامس، وفي جميع المعاملات. This investigation was carried out to study the effect of growth supplements addition to compost media on mushroom production. Supplements include cotton seed cake, soybean cake and wheat bran, added at 3, 6, and 9% (dry weight base). Supplements additions were done at mycelium spawning and after incubation stages (casing stage). Mushroom production was recorded weekly and calculated over the whole growth period. The results indicated a significant increase in mushroom production in all treatments of growth supplement compared with the control in both addition stages. The highest production was given by treatment receiving 9% cotton seed cake (36.9 kg mushroom/100 kg compost), followed by treatments receiving 6% either soybean or cotton seed cake in which mushroom productions registered 34.25 and 34 kg/100 kg compost, respectively. Results also indicated a significant effect of supplements addition at the (casing stage) with a production of (32.44 kg/100 kg compost) compared to (30.2 kg/100 kg compost) when supplements were added at mycelium spawning stage. Mushroom production was significantly increased in the first week at both addition stages, being greater with application at covering stage than mycelium planting stage. Thereafter, mushroom weekly production decreased in all treatment reaching the lowest at the fifth week.